Boosting Quality Registries with Clinical Decision Support Functionality - Wannheden, Carolina; Hvitfeldt-Forsberg, Helena; Eftimovska, Elena; Westling, Katarina; Ellenius, Johan (Methods of Information in Medicine, 2017)
Background: The care of HIV-related tuberculosis (HIV/TB) is complex and challenging. Clinical decision support (CDS) systems can contribute to improve quality of care, but more knowledge is needed on factors determining user acceptance of CDS.Objectives: To analyze physicians’ and nurses’ acceptance of a CDS prototype for evidence-based drug therapy recommendations for HIV/TB treatment.Methods: Physicians and nurses were involved in designing a CDS prototype intended for future integration with the Swedish national HIV quality registry. Focus group evaluation was performed with ten nurses and four physicians, respectively. The Unified Theory of Acceptance and Use of Technology (UTAUT) was used to analyze acceptance.Results: We identified several potential benefits with the CDS prototype as well as some concerns that could be addressed by redesign. There was also concern about dependence on physician attitudes, as well as technical, organizational, and legal issues.Conclusions: Acceptance evaluation at a prototype stage provided rich data to improve the future design of a CDS prototype. Apart from design and development efforts, substantial organizational efforts are needed to enable the implementation and maintenance of a future CDS system.
Keywords: Clinical decision support systems; drug therapy; quality registry; HIV; tuberculosis